18-Month Clinical Performance of a Bulk-Fill Composite Resin In NCCLS. (2022) - Guerra, L.; Neta, N.F. Coelho; Ruschel, V.C.; Baratieri, C.L.; Walter, R.; Junior, S. Monteiro
Abstract : Purpose/Aim: To evaluate the clinical performance of a bulk-fill composite resin in the restoration of non-carious cervical lesions (NCCLs) during 18 months of clinical service, and to compare its performance to other commercially available materials. Materials and Methods: Eighteen subjects in need of 143 restorations participated in the study. NCCLs were randomly assigned to three groups to be restored with 1) Durafill VS (Heraeus Kulzer); 2) Z100 (3 M Oral Care); or 3) SureFil SDR flow + (Dentsply Sirona). The internal aspect of the NCCLs were roughened with a diamond and Clearfil SE Bond 2 was applied following the selective etching protocol. Durafill VS and Z100 were inserted in increments that were up to 2 mm in thickness. The bulk-fill composite resin SureFil SDR flow + was applied in a single increment of up to 4 mm. Materials were light-activated according to the manufacturers recommendations and finished/polished immediately after placement. Restorations were performed by a single operator and were evaluated immediately after completion, and after 18 months by two independent evaluators. The clinical characteristics evaluated using the modified USPHS assessment criteria were retention, marginal adaptation, marginal discoloration, second caries, shade match, and texture. Results: All subjects were available for the 18-month evaluation. No restoration failed (no Charlie score) during the 18 months of clinical service. All restorations scored Alfa for retention and secondary caries. For marginal adaptation, the percentage of Alfa scores at 18 months was 77% (33/43) for DuraFill VS, 71% (37/52) for Z100, and 73% (35/48) for SureFil SDR flow +. In regard to marginal discoloration, 53% (23/43) of the Durafill VS restorations, 71% (37/52) of the Z100 restorations, and 65% (31/48) of the SureFil SDR flow + restorations were able to maintain the Alfa score during the 18-month evaluation. For shade match and texture, respectively, percentages of Alfa score at 18 months were 74% (32/43) and 58% (25/43) for Durafill VS; 73% (38/52) and 56% (29/52) for Z100; and 79% (38/48) and 58% (28/48) for SureFil SDR flow +. Conclusions: Restorations placed with Durafil VS, Z100, and SureFil SDR flow + showed acceptable clinical performance as no restoration failed during 18 months of clinical service. The implication of the Bravo scores during the first 18 months of clinical service in the longevity of the restorations at this time is unknown.